2003
DOI: 10.1210/jc.2002-021808
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistin (FIZZ3) Protein Is Increased in Obese Humans

Abstract: The role of resistin in obesity and insulin resistance in humans is controversial. Therefore, resistin protein was quantitated by ELISA in serum of 27 lean [13 women/14 men, body mass index (BMI) 21.7 +/- 0.4 kg/m(2), age 33 +/- 2 yr] and 50 obese (37 women/13 men, BMI 49.8 +/- 1.5 kg/m(2), age 47 +/- 1 yr) subjects. There was more serum resistin protein in the obese (mean +/- SEM: 5.3 +/- 0.4 ng/ml; range 1.8-17.9) than lean subjects (3.6 +/- 0.4 ng/ml; range 1.5-9.9; P = 0.001). The elevation of serum resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
268
9
19

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(318 citation statements)
references
References 18 publications
(26 reference statements)
22
268
9
19
Order By: Relevance
“…In contrast to some studies in adults, [6][7][8]18 the resistin levels did not differ between obese and lean children. The sample sizes in the studies in adults were similar 6 or smaller 7,8,18 as compared to our study.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In contrast to some studies in adults, [6][7][8]18 the resistin levels did not differ between obese and lean children. The sample sizes in the studies in adults were similar 6 or smaller 7,8,18 as compared to our study.…”
Section: Discussioncontrasting
confidence: 97%
“…The sample sizes in the studies in adults were similar 6 or smaller 7,8,18 as compared to our study. A too small sample size in our study to detect significant differences was excluded by a power analysis.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Nevertheless, despite the species differences outlined above, an increased plasma resistin concentration was observed in the serum of obese [16] or type 2 diabetics [17] and thiazolidinedione treatment resulted in decreased plasma resistin levels in patients with type 2 diabetes [18]. Furthermore, although some studies suggest a link between resistin and insulin sensitivity [19] others have failed to show an association with insulin resistance [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The identity of resistin amino acid sequences in mouse and human proteins is only 59% [6] and because of this incomplete homology resistin may have different physiological roles in different species [7]. In fact, studies in humans reported conflicting results, indicating decreased or increased resistin levels in obesity, opposite responses to insulin-sensitisers and contradictory correlations between resistin and markers of insulin resistance [8][9][10][11][12][13][14][15]. It has also been suggested that resistin plays a role in inflammatory conditions, because it is expressed in human macrophages [16] and because recent data have supported the existence of an independent association of resistin with the inflammatory factors IL-6 and C-reactive protein [17].…”
Section: Introductionmentioning
confidence: 99%